THE INFLUENCE OF COACHING AND SOCIAL GUIDANCE IMPLEMENTATION ON ADAPTIVE BEHAVIOR AMONG PSYCHOTIC CLIENTS: A STUDY AT THE PSYCHOTIC SOCIAL REHABILITATION CENTER IN EAST-JAKARTA - Mona Indriani; Adi Fahrudin (KHIDMAT SOSIAL: Journal of Social Work and Social Services, 2020)
This study reports the adaptive behavior of clients at a center for psychotic social rehabilitation in East Jakarta. Pre-Experiment Method and The Static Group Comparison design was used in this study. Eighty five (85) was selected using purposive sampling technique and divide in two groups were divided into two groups which 45 clients followed the coaching and social guidance program as experiment group, and 40 clients not yet follow as a control group.). The main research instrument used was adapted from Vineland Adaptive Behavior Scale (VABS). Based on the Mann Whitney U test, results of the study show that there are significant differences in term of communication skill, daily life skills, socialization skill, and motor skills between experiment and control group. These differences occur because of the provision of positive coaching and social guidance activities from professional social workers in the institution. The implication of these findings also discussed in the context of the provision of coaching and social guidance for schizophrenia clients by social workers in IndonesiaKeywords: psychotic, client, coaching and social guidance, adaptive behavior